Poromechanics V 2013
DOI: 10.1061/9780784412992.061
|View full text |Cite
|
Sign up to set email alerts
|

One-Way versus Two-Way Coupling in Reservoir-Geomechanical Models

Abstract: Procedures to couple reservoir and geomechanical models are reviewed. The focus is on immiscible compressible non-compositional reservoir -geomechanical models. Such models require the solution to: coupled stress, pressure, saturation and temperature equations. Although the couplings between saturation and temperature with stress and fluid pressure are "weak" and can be adequately captured thru staggered (fixed point) iterations, the coupling between stress and pressure equations are "strong" and require speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 26 publications
(20 reference statements)
0
23
0
Order By: Relevance
“…The preconditioner operator scriptP is applied to the residual bold-italicRk=(bold-italicBscriptAbold-italicXk)—that is, to the correct discrete residual form of the equilibrium and continuity equations. This fact is overlooked in . The algorithm for applying scriptP1 to the residual vector R k is bold-italicY=scriptP1bold-italicRk[]YuYp=[]A1A1B1S~10S~1[]Ru,kRp,k which takes advantage of the block‐triangular nature of scriptP by first updating the pressure components ( Y p ) followed by the displacement components ( Y u ) as follows: bold-italicYp=trueS~1bold-italicRp,k, bold-italicYu=A1()bold-italicRu,kB1bold-italicYp. It is well known that a necessary and sufficient condition for the convergence of stationary iterative methods is that the spectral radius, ρ , of the iteration matrix, scriptM, is smaller than unity in magnitude .…”
Section: Numerical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The preconditioner operator scriptP is applied to the residual bold-italicRk=(bold-italicBscriptAbold-italicXk)—that is, to the correct discrete residual form of the equilibrium and continuity equations. This fact is overlooked in . The algorithm for applying scriptP1 to the residual vector R k is bold-italicY=scriptP1bold-italicRk[]YuYp=[]A1A1B1S~10S~1[]Ru,kRp,k which takes advantage of the block‐triangular nature of scriptP by first updating the pressure components ( Y p ) followed by the displacement components ( Y u ) as follows: bold-italicYp=trueS~1bold-italicRp,k, bold-italicYu=A1()bold-italicRu,kB1bold-italicYp. It is well known that a necessary and sufficient condition for the convergence of stationary iterative methods is that the spectral radius, ρ , of the iteration matrix, scriptM, is smaller than unity in magnitude .…”
Section: Numerical Modelmentioning
confidence: 99%
“…The preconditioner operator P is applied to the residual R k D .B AX k /-that is, to the correct discrete residual form of the equilibrium and continuity equations. This fact is overlooked in [35,45]. The algorithm for applying P 1 to the residual vector R k is…”
Section: Solution Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Further, it should be noted that the C m approximation used in conventional reservoir simulators provides a correct representation of the diffusion time, which is controlled by the following diffusion coefficient (e.g., ): cf MathClass-rel= k μfM λS MathClass-bin+ 2μS λS MathClass-bin+ 2μS MathClass-bin+ b2M1emquad1emquadλS MathClass-bin+ 2μS MathClass-rel= KS MathClass-bin+ 4 3GS However, this is not the case with the scheme proposed by Kim et al , which therefore introduces undesirable distortions of the diffusion time and processes. Various one‐way coupling and one‐way iterative coupling strategies are discussed in detail in , where it is shown that one‐way iterative (sequential) integration of reservoir–geomechanical equations can work but requires an unreasonable number of iterations for accurate integration of strongly coupled equations, such as pressure and stress equations. This is not a surprise because it is well known that fixed‐point iterations (if they converge at all) always require a large number of iterations to converge.…”
Section: One‐way Coupling Solution Schemesmentioning
confidence: 99%
“…This strategy is in part motivated from the availability of established and robust commercial software for both multi-phase flow (Schlumberger, n.d.-a) as well as mechanical deformation (Schlumberger, n.d.-b). Although some of these coupled approaches can be shown to be stable (Kim, Tchelepi, & Juanes, 2011b) and convergent (Mikelić, Wang, & Wheeler, 2014), in general it is desirable to consider a tighter coupling between flow and mechanics (Prevost, 2013).…”
Section: Introductionmentioning
confidence: 99%